Avaliação dos parâmetros hematológicos, bioquímicos e parasitológicos decorrentes da infecção por Ancylostoma ceylanicum em hamsters (Mesocricetus auratus) submetidos à dieta hipoprotéica - Carina de Paula Pacanaro Oliveira (2013)
Hookworms infect an estimated 740 million people worldwide and can lead to severe clinical manifestations in their host. Prospective cohort studies in Brazil show high rates of reinfection in malnourished children that had been treated, in comparison with wellnourished children. In addition, geohelminths infections worsen the nutritional status ofthe population involved. This study aims to clarify the effects of the nutritional status of the host in the course of infection by Ancylostoma ceylanicum and how infection affects the nutritional status of the host, using an experimental model. Immunocompetent hamsters (Mesocricetus auratus) are permissible to the development of the hookworm A. ceylanicum, which can also infect humans. Thus, infective third stage larvae (L3) administered orally in hamster develops into adult worms in the host small intestine. In this experiment, we evaluated the influence of the malnutrition state, in hamsters submitted to a low protein diet and infected with A. ceylanicum. We used four experimental groups: Groups CN and CI: Control Groups fed with diets prepared with optimum amount of protein (25,0%) and Groups DN and DI: Malnourished Groups that received a low-protein diet, prepared with 6,0% protein. All groups were fed ad libitum with their respective diets for four weeks prior to infection by A. ceylanicum, and all groups remained in their diets until the end of the experiment. The animals in groups CI and DI were orally infected with 50 L3, by gavage, 28 days after initiation of treatment with specific diets. Twenty two days after infection, the animals were euthanized and the adult worms recovered from the small intestine to number quantification and sexing. The following parameters were evaluated: weight, complete blood count, fasting glucose, content body lipids, total protein in serum and number of eggs per gram of feces (EPG). It was observed that the infected malnourished group showed more severe pathogenesis demonstrated by significant decrease in hemoglobin concentration, erythrocyte number and packed cell volume, compared to the non-infected malnourished group. It was observed a higher recovery of adults parasites and number of eggs to the undernourished group compared to the control group, however, thefemales oviposition rate of from the DI group was lower than the CI group. These founds confirms the hypothesis that the host nutritional condition presents a high influence in the course of the infection, aggravating the pathogenesis.